Transcriptome Analysis of the Cerebellum of Mice Fed a Manganese-Deficient Diet - Seo, Young Ah; Choi, Eun-Kyung; Aring, Luisa; Paschall, Molly; Iwase, Shigeki (Frontiers in Genetics, 2020)
Manganese (Mn) is required for brain function and development. Epidemiological studies have found an association between both low and high levels of Mn and impaired neurodevelopment in children. Recent genetic studies have revealed that patients with congenital Mn deficiency display severe psychomotor disability, cerebral and cerebellar atrophy. Although the impact of Mn on gene expression is beginning to be appreciated, Mn-dependent gene expression remains to be explored in vertebrate animals. Mn is primarily acquired through diet; therefore, the goal of this study was to define the impact of feeding low levels of Mn on brain metal levels and to probe the molecular dysfunction associated with low Mn levels in an unbiased manner using a mouse model. We interrogated gene expression changes in the Mn-deficient mouse brain at the genome-wide scale by RNA-seq analysis of the cerebellums of mice fed either low or normal Mn diets. A total of 137 genes were differentially expressed in Mn-deficient cerebellums compared with Mn-adequate cerebellums (Padj < 0.05). Mn-deficient mice displayed downregulation of key pathways involved with “focal adhesion,” “neuroactive ligand-receptor interaction,” and “cytokine-cytokine receptor interaction” and upregulation of “herpes simplex virus 1 infection,” “spliceosome,” and “FoxO signaling pathway.” Reactome pathway analysis found upregulation of the splicing-related pathways and transcription-related pathways, as well as downregulation of “metabolism of carbohydrate,” and “extracellular matrix organization,” and “fatty acid metabolism” reactomes. Dietary Mn deficiency alters the mouse cerebellum transcriptome. Recurrent identifications of splicing-related pathways suggest that Mn deficiency leads to upregulation of splicing machineries and downregulation of diverse biological pathways.